Ocean‐Sea Ice Processes and Their Role in Multi‐Month Predictability of Antarctic Sea Ice. Issue 8 (25th April 2022) - Libera, Stephy; Hobbs, Will; Klocker, Andreas; Meyer, Amelie; Matear, Richard
Abstract: Antarctic sea ice is a critical component of the climate system and a vital habitat for Southern Ocean ecosystems. Understanding the underlying physical processes and improving Antarctic sea ice prediction is of broad interest. Using the model data, we investigate sea ice and upper ocean predictability at interannual timescales in the Weddell Sea region. We find that oceanic predictability is largely confined to the Winter Water layer and responds to seasonal modifications of the water column, mainly driven by sea ice processes. Predictability depends not only on the depth of the Winter Water layer, but also on how strongly stratified its base is. Predictability is lost when warm Circumpolar Deep Water with no sea ice‐related memory entrains into the mixed layer. We show the strong dependence of sea ice predictability on the local upper ocean vertical structure, which suggests that both are likely to change in a warming climate. Plain Language Summary: Antarctic sea ice is a critical component of climate and a vital habitat for Southern Ocean ecosystems. Therefore, understanding the drivers and physical processes influencing Antarctic sea ice, and being able to predict Antarctic sea ice is of broad interest. We assess the predictability of sea ice and underlying upper ocean in the Weddell Sea region of the Southern Ocean using the model data. We find that sea ice processes influence the upper ocean temperature, and these thermal signatures linger in the ocean producing sea ice predictability over multiple months. Here, we show that the oceanic memory in the upper ocean is largely found within the Winter Water layer (i.e., cold water layer formed during sea ice formation). Oceanic memory and sea ice predictability are suddenly lost when warm deep waters from the ocean interior entrain into the surface mixed layer in mid‐winter. This limit to sea ice predictability has not been explored before, and it shows the strong dependency of sea ice predictability in a region to its local vertical structure of oceanic properties and their seasonal evolution. This implies that changes to upper ocean properties in a warming climate can likely alter the sea ice predictability patterns in the future. Key Points: Sea ice predictability in the Weddell Sea is strongly determined by temperature and salinity profiles of the underlying upper ocean Every winter, the timing of the loss of sea ice predictability is defined when deep water is entrained into the mixed layer Sea ice predictability depends not only on the depth of the Winter Water layer but also on how strongly stratified its base is